2009
DOI: 10.1212/01.wnl.0000338629.01627.54
|View full text |Cite
|
Sign up to set email alerts
|

MRI in the diagnosis of pediatric multiple sclerosis

Abstract: We propose modifications to the currently established McDonald MRI criteria for lesion dissemination in space that will enhance the diagnostic accuracy of these criteria for multiple sclerosis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
2
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 25 publications
3
75
2
5
Order By: Relevance
“…recent mri studies involving computer-based lesion detection indicate similar absolute lesion burdens-as measured by t2 lesion volume or by total lesion count-in children with demyelina tion and adults with ms. 13,18,26 However, the distributions of lesions may show important distinctions, with a greater pre dilection for pontine and a reduced prevalence of periventricular locations in children. 27 laboratory studies show similar spinal fluid findings of oligoclonal banding between adults and children with ms, 28,29 although very young patients with pediatric-onset disease can have negative spinal fluid findings at onset. immunological responses, as measured by immunological studies of t-cell proliferation 30 and B-cell-derived antibodies, 31 demonstrate that pediatric inflammatory responses seem no less robust than those seen in adult-onset ms and, in some children, appear even stronger than responses in adult ms cohorts.…”
Section: Key Pointsmentioning
confidence: 77%
“…recent mri studies involving computer-based lesion detection indicate similar absolute lesion burdens-as measured by t2 lesion volume or by total lesion count-in children with demyelina tion and adults with ms. 13,18,26 However, the distributions of lesions may show important distinctions, with a greater pre dilection for pontine and a reduced prevalence of periventricular locations in children. 27 laboratory studies show similar spinal fluid findings of oligoclonal banding between adults and children with ms, 28,29 although very young patients with pediatric-onset disease can have negative spinal fluid findings at onset. immunological responses, as measured by immunological studies of t-cell proliferation 30 and B-cell-derived antibodies, 31 demonstrate that pediatric inflammatory responses seem no less robust than those seen in adult-onset ms and, in some children, appear even stronger than responses in adult ms cohorts.…”
Section: Key Pointsmentioning
confidence: 77%
“…1 Over the past few years, magnetic resonance imaging (MRI) techniques have been applied to define the features of paediatric MS patients. 2,3 While conventional MRI has played a key role in the diagnostic work-up of patients with paediatric MS, 3 advanced MRI techniques have contributed to gradation of the extent of 'diffuse' brain damage in these patients. Overall, studies using proton MR spectroscopy, magnetization transfer MRI and diffusion tensor MRI [4][5][6][7] have suggested that, compared with their adult counterparts, patients with paediatric MS have less involvement of the brain normal-appearing white matter (NAWM) and cord normal-appearing tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In our patient, the lack of altered consciousness or signs of encephalopathy may favor the diagnosis of MS, although encephalopathy could occur in MS [5][6][7]. On the other hand, the absence of oligoclonal bands in CSF in acute stages and predominant involvement of the cortices and subcortical white matter without periventricular involvement may be more characteristic of ADEM [5,[7][8][9][10][11]. Pathologically, perivenous demyelination and discrete confluent demyelination have been regarded as the hallmark of ADEM and MS respectively [3].…”
Section: Discussionmentioning
confidence: 97%